Mulheres ao longo do processo de surgimento do esporte moderno em Belém do Pará: décadas finais do século XIX aos anos de 1910 - FERREIRA, Verônica Moreira Souto (2019)
The present work deals with the participation of women in the process of the emergence of modern sport in Belém do Pará (late nineteenth century to 1910 years), having as a research problem the following question: What is the role of women in the process of the emergence of sport modern in Belém do Pará in the final decades of the nineteenth century to the years 1910? The objective of the research was to analyze the participation of women throughout the emergence of modern sport in Belém, in the final decades of the nineteenth century to 1910, and the specific objectives were: a) To understand the historical time of the final decades of the nineteenth century to the years of 1910 with regard to the insertion of women in the universe of sociabilities in Belém do Pará; b) To analyze how the origin of the women's sports practices occurred (final decades of century XIX to years of 1910) in Belém of Pará; c) Punctuating sports practiced by women in Belém do Pará (late nineteenth century to 1910 years); d) Understanding sport as a field of sociability for Belenian women in the final decades of the nineteenth century to the years 1910. Characterized as a historiographic study of documentary character, we adopted Cultural History as the guiding force of our analyzes. The sources consulted were newspapers of the period evoked, belonging to the collections of the Brazilian Digital Library and the Arthur Vianna Public Library. We found in the newspapers researched several indications of the progressive participation of women in the sociabilities of a modernizing Bethlehem. Among the various amusements and social events available in that period, we visualized the presence of women in dances, bullfights, horse races and sports competitions, especially crocket, skating, shooting, swimming, gymnastics, soccer, cycling and regattas, role of spectators and, later, as practitioners of the modalities. At the end of the research, we can affirm that the process of modernization of the city of Belém and the emergence of a new urban culture, following the European molds, allowed the expansion of the field of feminine sociabilities, with sports practices taking center stage in this process. In addition, it was possible to identify a demarcation of roles and social attributions, and it is up to women to occupy the role of grace, beauty, and gentleness from the masculine gaze at the sources and, roughly, from the coeval mentalities.